Regulation of drug-metabolizing enzymes by sex-related hormones: clinical implications for transgender medicine. (July 2022) - Le, An; Huang, Kai J.; Cirrincione, Lauren R.
Abstract : Transgender medicine is a diverse and growing clinical field with unmet gaps in pharmacological knowledge. Hormone therapy (testosterone or estrogen treatment), one part of the standard of medical care for transgender adults, aligns secondary sex characteristics with an individual's gender identity and expression. Despite established effects of sex steroids on drug-metabolizing enzyme expression and activity in vitro and in animal models, the effect of long-term, supraphysiological sex hormone treatment on drug metabolism in transgender adults is not yet established. Here, we synthesize available in vitro and animal model data with pharmacological concepts in transgender medicine to predict potential effects of sex steroids on drug-metabolizing enzymes, and their relationship with potential hormone–drug interactions, in transgender medicine. Highlights: Transgender people represent a growing population who may choose to undergo long-term hormone therapy for medical care that includes testosterone or estradiol treatment. Based on in vitro and animal model data, hormone therapy may alter cytochrome P450 (CYP)- or uridine diphosphate-glucuronosyltransferase (UGT)-mediated drug metabolism in transgender adults. Most available in vitro and animal model data suggest that estradiol treatment induces the expression (mRNA and protein levels) and activities of CYP3A4, CYP2B6, UGT1A1, and UGT1A4, while inhibiting CYP1A2 expression and activity in transgender adults. No clinically significant effects of testosterone treatment on CYP- or UGT-mediated drug metabolism can be predicted based on available in vitro or animal model data.